Trazos de sangre y fuego Bio-Necropolítica y juvenicidio en América Latina - Valenzuela Arce, José Manuel (Afrontar las crisis desde América Latina, 2019)
In these times the processes of poverty and social inequality have increased, as well as the scenarios of violence and death that involve people, the planet and life itself. The destructive features of the late international capitalist order have placed the life-death relationship at the center of social, humanistic, ecological and artistic discussion. This book invites us to rethink the contemporary world through the discussion on biopolitics, necropolitics, juvenicide and narcoculture, and offers an analysis of the conformation of the features that emphasize the inequalities, distinctive of some sectors of the middle and upper classes.